CRIMINAL DELINQUENCY – CYBERSTALKING: CHARACTERISTICS OF OBJECT AND OBJECTIVE SIDE - Ķinis, Uldis (Administrative and Criminal Justice, 2018)
On January 2018 significant amendments to the Criminal Law and the Law On the Procedure for Application of the Criminal Law came into force in Latvia. These changes not only in the first time introduce the criminal responsibility for the emotional violence, but also determine the procedure for assessing emotional disparity, equating the effects to telepathic injuries.In the article, the author reviews a modality of crime “persecution” - cyber-persecution. Although the legislator in the annotation of the law provides that the article also shall be applicable to acts committed in cyberspace, at the same time, the author indicates some problems that may arise due to the narrow interpretation of the law by the law enforcement. The purpose of the article is to study the object (protected legitimate interest) and the objective side (actus reus) of the offense - cyber-stalking. For purposes of research, several methods have been used. The method of comparative analysis, for examination and comparison of external and international regulations. Methods of legal interpretation used to disclose the differences between the understanding of the written text of the definition of the crime and what ought to be understood in the meaning of the norm. Finally, the author presents the conclusions and proposals on the application of the norm.